Respuesta :

Answer:

(ab - 6)(2ab + 5)

Step-by-step explanation:

Assuming you require the expression factorised.

2a²b² - 7ab - 30

Consider the factors of the product of the coefficient of the a²b² term and the constant term which sum to give the coefficient of the ab- term

product = 2 × - 30 = - 60 and sum = - 7

The factors are - 12 and + 5

Use these factors to split the ab- term

= 2a²b² - 12ab + 5ab - 30 ( factor the first/second and third/fourth terms )

= 2ab(ab - 6) + 5(ab - 6) ← factor out (ab - 6) from each term

= (ab - 6)(2ab + 5) ← in factored form

ACCESS MORE